Feeding Ecology of Asian Green Mussel (Perna viridis): Influences of Sexes, Sizes, Habitats and Seasons - Teuku Haris Iqbal (Prince of Songkla University, Pattani Campus, 2019)
Thesis (M.Sc.(Fishery Technology))--Prince of Songkla University, 2017